(untitled) (Pulse, 2011)
Aim and Objective: Dysembryoplastic neuroepithelial tumour is an unusual brain tumour with varied incidence commonly occured in younger age group. We report a 16-year old female diagnosed as a case of dysembryoplastic neuroepithelial tumour. Clinical presentation: A 16 year old female was examined for headache and convulsion for two months. MRI revealed a brain tumour which was later confirmed as dysembyroplastic neuroepithelial tumour by histopathological examination. DOI: http://dx.doi.org/10.3329/pulse.v4i1.6968 Pulse Vol.4 January 2010 p.43-44